Growth Temperature Influence on Lipids and Photosynthesis in Lepidium sativum - Sattari Vayghan, Hamed; Tavalaei, Shahrzad; Grillon, Armand; Meyer, Léa; Ballabani, Gent; Glauser, Gaëtan; Longoni, Paolo (Frontiers in Plant Science, 2020)
Temperature has a major impact on plant development and growth. In temperate climates, the seasonal temperature displays large variations that can affect the early stages of plant growth and development. Sessile organisms need to be capable of responding to these conditions, so that growth temperature induces morphological and physiological changes in the plant. Besides development, there are also important molecular and ultrastructural modifications allowing to cope with different temperatures. The chloroplast plays a crucial role in plant energetic metabolism and harbors the photosynthetic apparatus. The photosynthetic light reactions are at the interface between external physical conditions (light, temperature) and the cell biochemistry. Therefore, photosynthesis requires structural flexibility to be able to optimize its efficiency according to the changes of the external conditions. To investigate the effect of growth temperature on the photosynthetic apparatus, we followed the photosynthetic performances and analyzed the protein and lipid profiles of Lepidium sativum (cress) grown at three different temperatures. This revealed that plants developing at temperatures above the optimum have a lower photosynthetic efficiency. Moreover, plants grown under elevated and low temperatures showed a different galactolipid profile, especially the amount of saturated galactolipids decreased at low temperature and increased at high temperature. From the analysis of the chlorophyll a fluorescence induction, we assessed the impact of growth temperature on the re-oxidation of plastoquinone, which is the lipidic electron carrier of the photosynthetic electron transport chain. We show that, at low temperature, along with an increase of unsaturated structural lipids and plastochromanol, there is an increase of the plastoquinone oxidation rate in the dark. These results emphasize the importance of the thylakoid membrane composition in preserving the photosynthetic apparatus under non-optimal temperatures.